A preliminary check list of macromycetes in northern Tunisia. (2nd January 2018) - Ouali, Z.; Compagno, R.; Sbissi, I.; Gargano, M. L.; Rhaiem, A.; Ben Naceur, M.; Venturella, G.; Jaouani, A.
Abstract: Within the last decade, checklists of fungi of several countries have been published or updated. Nevertheless, no checklists of macromycetes have hitherto been published for Tunisia (North Africa) apart from a mycocoenological study reporting 34 listed species. This work presents a list of macromycetes collected from January 2014 to March 2015 in six governorates of northern Tunisia. One hundred and twenty-three species (117 basidiomycetes and six ascomycetes) belonging to 78 genera and 46 families were recorded.